A system verilog approach for verification of memory controller - Sowmya K B; Gagana P (International Journal of Reconfigurable and Embedded Systems (IJRES), 2020)
Memory performance has become the major bottleneck to improve the overall performance of the computer system. By using memory controller, there is effective control of data between processor and memory. In this paper, a memory controller for interfacing Synchronous Static Random Access Memory (SSRAM), Synchronous Dynamic Random Access Memory (SDRAM), Read Only Memory (ROM) and FLASH which is Electrically Erasable Programmable Read-Only Memory is designed and a coverage driven Constraint random verification environment is built for the designed memory controller. Verification plays an important role in any design flow as it is done before silicon development. It is done at time of product development for quality checking and bug fixing in design.